Dealing with global environmental change: the design and validation of the GEC attitude scale. Issue 1 (2nd January 2021) - Varela-Losada, Mercedes; Pérez-Rodríguez, Uxío; Lorenzo-Rial, María; Vega-Marcote, Pedro; Reid, Alan
Abstract: Global Environmental Change (GEC) refers to alterations in the structure and functioning of Earth Systems arising from the detrimental effects of human activities in the biophysical and socioeconomic spheres. This study constructs and validates a scale to measure GEC-related attitudes (SGEC) for use with educators and the public. The results, which were validated by a wide sample ( N = 962), show a factor structure of four well-defined interrelated factors (χ 2 = 268.75; p < .000; χ 2 /gl = 1.84; AIC = 394.75; CFI = .934; RMSEA = .042 [.034 .050]), with reliability (α = .817, glb = .894, Ω = .855). The factors were Social Responsibility (SR), Need to Cope (NC), Individual Responsibility (IR), Anthropogenic Origin (AO). These factors and findings suggest the SGEC can provide relevant information on: (i) awareness of the anthropogenic origins of GEC, (ii) perceptions of the need to deal with GEC, and attributions of (iii) social and (iv) individual responsibility in solving and mitigating GEC-related problems.